An assessment of the resistance of various bean cultivars to an isolate of bean common mosaic virus from the Transvaal and Natal - Edington, Brian Ross (My University, 2015)
One of he economically important diseases of beans in 3outh Africa is caused by bean common mosaic virus. The virus occurs as a number z t .iso1ates> world-wide and breeding for resistance is aided by the id ’fixation of the prevalent strain. The isolate prevalent in South Africa was found to belong to virus pathogenicity group V. It was identified by inoculating a set of bean differential hosts recommended by Drijfhout (1978). Samples collected from the Transvaal and parts of Natal did not differ significantly in symptom development in response to the tests. The South African isolate causes a temperature-dependant systemic necrosis in plants with the I-gene and without the recessive gene resistance. It was still capable of inducing necrosis in "Nep 2", host resistance group 8, 60 hours post inoculation and 84 hours for "Peru 0257", host resistance group 9, when it transferred from a cold (20°C day) to a warm glasshouse (30°C). An hour at 30°C was sufficient to induce necrosis in "Nep 2". The results of a speckled sugar bean breeding programme are included and further suggestions are made for breeding for resistance and the elimination of bean common mosaic virus as a problem in South Africa.